1995
DOI: 10.1007/bf00186543
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolutionary analysis of the ywvz/7B globin gene cluster of the insect Chironomus thummi

Abstract: We report the sequence of 8.1 kb of DNA containing the 3' end of one and seven other complete intronless globin genes from the YWVZ/7B locus of the dipteran Chironomus thummi thummi. One of these (ctt-v) appears to be a pseudogene by virtue of a premature termination codon, whereas the others encode apparently functional globin polypeptides. taken together with previously published data, the C. th. thummi YWVZ/7B locus codes for at least 11 globins, five of which differ from one another by no more than two ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 24 publications
(43 reference statements)
0
15
0
Order By: Relevance
“…Similar gene loss events by unequal or intra-chromosomal crossing-over have been reported e.g. in the globin gene family of the insect Chironomus (Trewitt et al, 1995), and recombination is known to produce mosaic sequences via heteroduplex formation and gene conversion (Bollag et al, 1992).…”
Section: Gbx -Duplication and Non-functionalization?mentioning
confidence: 81%
“…Similar gene loss events by unequal or intra-chromosomal crossing-over have been reported e.g. in the globin gene family of the insect Chironomus (Trewitt et al, 1995), and recombination is known to produce mosaic sequences via heteroduplex formation and gene conversion (Bollag et al, 1992).…”
Section: Gbx -Duplication and Non-functionalization?mentioning
confidence: 81%
“…thummi and the ancestor to ctn-ORFB in C. tentans. We Trewitt et al 1995 conclude that the five globin genes in C. tentans and the six genes in C. th. thummi are descended from five genes (filled squares in Fig.…”
Section: Orthologous Globin Genesmentioning
confidence: 99%
“…thummi globin amino acid sequences (Goodman et al 1988), three genes reported here are novel, encoding globins whose protein products have not yet been isolated. Building on a systematic approach to naming chironomid globin genes Trewitt et al 1995), these are called ctt-11, ctt-12, and ctt-13 (the numbers 1-10 being previously assigned). The historical use of Roman numerals to name globin polypeptides sequenced at the amino acid level is retained.…”
Section: Nomenclaturementioning
confidence: 99%
See 2 more Smart Citations